2018
DOI: 10.1007/s00125-018-4651-x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CXCR3 expression on memory B cells in individuals with long-standing type 1 diabetes

Abstract: Aims/hypothesisIslet-specific autoantibodies can predict the development of type 1 diabetes. However, it remains unclear if B cells, per se, contribute to the causal pancreatic immunopathology. We aimed to identify phenotypic signatures of disease progression among naive and memory B cell subsets in the peripheral blood of individuals with type 1 diabetes.MethodsA total of 69 participants were recruited across two separate cohorts, one for discovery purposes and the other for validation purposes. Each cohort c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Alterations within CD19 + B cell subsets were only found in patients with HT despite that autoantibodies are also present in T1D, GD and AD. Previous studies addressing peripheral B cells in T1D and GD have reported that frequencies were similar compared to HC (32)(33)(34) or that functional responses toward autoantigens were changed (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…Alterations within CD19 + B cell subsets were only found in patients with HT despite that autoantibodies are also present in T1D, GD and AD. Previous studies addressing peripheral B cells in T1D and GD have reported that frequencies were similar compared to HC (32)(33)(34) or that functional responses toward autoantigens were changed (35,36).…”
Section: Discussionmentioning
confidence: 96%
“…Spanning-tree progression analysis of density-normalised events Live T cells were identified in serial gates as singlets, lymphocytes, LIVE/DEAD Fixable Aqua − , CD19 − , CD3 + events and gated as CD4 + , CD8 + , CD4/CD8 double-positive, or CD4/CD8 double-negative cells using FlowJo. Compensated flow cytometry files were exported for Spanning-tree Progression Analysis of Density-normalized Events (SPADE) using fixed settings (K-means algorithm, 100 clusters, Arcsinh transformation with cofactor 150) in SPADE software version 3.0 [6,20,21]. Expression of cell surface markers (CD3, CD4, CD8, CD27, CD57, CD95, CD45RA, CD127, CXCR3 and programmed cell-death protein 1 [PD-1]) was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…People with type 1 diabetes display altered frequencies and function of a number of lymphocyte subsets, as well as different expression levels of surface markers; frequency and suppressive ability of Tregs are reduced in type 1 diabetes [3]. Expression of C-X-C motif chemokine receptor 3 (CXCR3) is reduced on CD3 + T cells in individuals with long-standing type 1 diabetes [4][5][6]. Although beta cellautoreactive CD8 + T cells are found in healthy volunteers, these CD8 + T cells from people with type 1 diabetes have a more differentiated phenotype that includes T SCM [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine CXCL10 is functionally classified as an inflammatory chemokine. The role of the CXCL10/CXCR3 axis in the immunopathogenesis of type 1 diabetes has been extensively studied with the blockade of the CXCL10/CXCR3 system considered as a promising therapeutic target [30,31].…”
Section: Discussionmentioning
confidence: 99%